Blue-Enriched White Light Therapy Reduces Fatigue in Survivors of Severe Traumatic Brain Injury: A Randomized Controlled Trial. Issue 2 (March 2020) - Quera Salva, Maria-Antonia; Azabou, Eric; Hartley, Sarah; Sauvagnac, Rebecca; Leotard, Antoine; Vaugier, Isabelle; Pradat Diehl, Pascale; Vallat-Azouvi, Claire; Barbot, Frederic; Azouvi, Philippe
Abstract : Objective: Fatigue is one of the disabling sequelae of traumatic brain injury (TBI), with repercussions on quality of life, rehabilitation, and professional reintegration. Research is needed on effective interventions. We evaluated efficacy of blue-enriched white light (BWL) therapy on fatigue of patients with severe TBI. Setting: Physical Medicine and Rehabilitation and Physiology departments of University hospitals. Participants: Adult patients with fatigue symptoms following severe TBI, Fatigue Severity Scale (FSS) score 4 or more, Epworth Sleepiness Scale (ESS) score 10 or more, and/or Pittsburgh Sleep Quality Index (PSQI]) more than 5 were randomly assigned to one of 2 parallel groups: a BWL therapy group, with 30-minute exposure to waking white light enriched with blue for 4 weeks, and a group without light therapy (N-BWL), no light. Design: Randomized controlled trial. ClinicalTrials.gov number: NCT02420275. Main Measures: The primary outcome measure was the response of the FSS to 4 weeks of treatment. In addition, we assessed latency change of the P300 component of event-related potentials before and after therapy. Results: Significant improvement in the FSS score ( P = .026) was found in the BWL group compared with the N-BWL group. Conclusion: BWL phototherapy reduces fatigue in patients with severe TBI.